Embedding sulfur in nanoporous carbon for lithium-sulfur batteries. - Wei, Shuya. (2013)
The lithium–sulfur battery has been under intense scrutiny for over two decades, due to the possibility of offering high gravimetric capacities and theoretical energy densities ranging up to five times beyond conventional Li-ion systems. Herein, we report two types of nanoporous carbons and their use as carbon hosts to incorporate sulfur for Li-S batteries. One is the facile synthesis of microporous carbon polyhedrons (MPCPs) by using unique MOF polyhedrons as both the template and precursor and the other is synthesis of mesoporous CMK-3 carbon nanorods (CNRs) by using mesoporous silica molecular sieve SBA-15 as template. The as-prepared MPCPs with abundant and uniform micropores are suitable for confining sulfur, and serve well as an ideal subject for investigating the electrochemical behaviors of sulfur embedded in microporous carbon. The CMK-3 carbon nanorods with ordered mesoporous channels exhibit good behavior for confining sulfur and stable electrochemical performance as well. Comparative investigations have been carried out to reveal the effects of several important parameters, such as the sulfur loading temperature, sulfur content, the electrolyte and polymer coating, which offer the opportunity to improve the electrochemical performance of the composite material. Under optimized condition, the MPCP/sulfur and CNR/sulfur composite can deliver stable cycling performance.